How agripreneurs gain access to finance - Hosenally, Nawsheen (Technical Centre for Agricultural and Rural Cooperation, 2018)
Young agripreneurs share their experience on accessing finance for their businesses. These include bootstrapping, grants from competitions, and loan from friends, among others.